Performance of Hybrid Steel Fibers Reinforced Concrete Subjected to Air Blast Loading - Mohammed Alias Yusof; Norazman Mohamad Nor; Ariffin Ismail; Ng Choy Peng; Risby Mohd Sohaimi; Muhammad Azani Yahya (Advances in Materials Science and Engineering)
This paper presents the results of the experimental data and simulation on the performance of hybrid steel fiber reinforced concrete (HSFRC) and also normal reinforced concrete (NRC) subjected to air blast loading. HSFRC concrete mix consists of a combination of 70% long steel hook end fibre and also 30% of short steel hook end fibre with a volume fraction of 1.5% mix. A total of six concrete panels were subjected to air blast using plastic explosive (PE4) weighing 1 kg each at standoff distance of 0.3 meter. The parameters measured are mode of failure under static and blast loading and also peak overpressure that resulted from detonation using high speed data acquisition system. In addition to this simulation work using AUTODYN was carried out and validated using experimental data. The experimental results indicate that hybrid steel fiber reinforced concrete panel (HSFRC) possesses excellent resistance to air blast loading as compared to normal reinforced concrete (NRC) panel. The simulation results were also found to be close with experimental data. Therefore the results have been validated using experimental data.